Big Data Implementation and Use for Business - Usanto, Usanto (Devotion : Journal of Research and Community Service, 2022)
The rapid development of information technology, especially in terms of collecting and storing large data (big data), has opened up new opportunities in various business fields. This research aims to analyze and describe the implementation and utilization of big data in the context of Shopee's e-commerce business. This research uses qualitative research methods. The data collection technique was carried out by literature study obtained from Google Schoolar and observation of the Shopee platform. The data obtained was then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that big data can be implemented with Product Introduction and Personalization, optimization of offers and promotions, and inventory management. The benefits of this implementation include helping to identify patterns, trends, preferences, and user behavior. In addition, it creates a more personalized shopping experience and motivates more purchases. Big data also helps Shopee in optimizing offers, promotions, product discounts, item availability, and increasing sales conversions.